Spectrophotometric determination of the sulfhydryl containing drug mesna - Rim S. Haggag; Dina A. Gawad; Saeid F. Belal; Hadil M. Elbardisy (Faculty of Pharmacy, Cairo University, 2016)
Four simple and sensitive spectrophotometric methods were developed for the determination of the sulfhydryl containing drug mesna (MSN). Methods I and II rely on nucleophilic aromatic substitution reactions using two UV tagging reagents namely: 4-chloro-7-nitrobenzo-2-oxa-1,3-diazole (NBD-Cl) for method I and 2,4-dinitrofluorobenzene (DNFB) for method II. Both reactions took place in alkaline buffered medium and the obtained yellowish products were measured at 414 and 332 nm for methods I and II, respectively. Methods III and IV are indirect spectrophotometric methods based on the suppressive effect of MSN on the absorption of two ternary complex systems which are composed of 1,10-phenanthroline, silver and eosin for method III and 1,10-phenanthroline, silver and bromopyrogallol red for method IV. The decrease in absorbance of the ternary complexes was measured at 547 and 635 nm for methods III and IV, respectively. All the experimental parameters affecting these reactions were carefully studied and optimized. The methods were validated as per the ICH guidelines. The methods were applicable in the linearity ranges 4-18 μg/mL for method I, 4-16 μg/mL for method II, 0.25-2.25 μg/mL for method III and 0.25-1.75 μg/mL for method IV. The proposed methods were successfully applied for the analysis of MSN in its commercial ampoules and no interference was encountered from the present excipients as indicated by the satisfactory percentage recoveries. The results obtained were in a good agreement with those obtained from a previously published method of the investigated drug.